Phosphorus status of some Ethiopian soils. III. Evaluation of soil test methods for available phosphorus - Mamo, T.; Haque, I. (1991)
Eight chemical methods were employed for estimating the available P in 32 Ethiopian soils using Phasey bean (Macroptilium lathyroides c.Murray) as a test crop grown in small pots in a glasshouse and the soil test values then correlated with plant characteristics. Olsens' method gave the highest correlation with percentage yield and P uptake in all three cuts and also was the most reliable giving 97 percent correct predictions. Warren and Cooke, and Truog methods were the next most useful methods. The Egner method was the least useful of all the methods for estimating available P from the soils. Olsen, Warren and Cooke, Truog methods are tentatively recommended for use in routine analysis for P in Ethiopian soils until regional experiments are established to define the superior chemical methods.